Neutrophil Gelatinase-Associated Lipocalin (NGAL) in predicting acute kidney injury following orthotopic liver transplantation: A systematic review. (November 2018) - Yeung, Arthur C.Y.; Morozov, Andrew; Robertson, Francis P.; Fuller, Barry J.; Davidson, Brian R.
Abstract: Background: Acute kidney injury (AKI) is common after orthotopic liver transplantation (OLT) usually occurring early post-transplant. Multiple causes include graft preservation injury, blood loss, hypotension but also severity of recipient liver disease. Early intervention in AKI has both short and long term patient benefits. Unfortunately there are no current clinical biomarkers of early AKI. Aim: To assess the value of NGAL in predicting AKI following OLT. Methods: Ovid MEDLINE and EMBASE were searched between the years of 2000 and 2017 for studies using keywords: Neutrophil Gelatinase Associated Lipocalin or NGAL variants combined with synonyms for liver transplantation. Results: 96 studies were identified. 11 studies including 563 patients were considered suitable for analysis. Both urinary (uNGAL) and plasma NGAL (pNGAL) measurement were found to predict AKI after liver transplantation. Optimal reported area under the receiver-operator characteristics curve (AUROC) values of 0.5–0.83 and 0.54–0.86 respectively. Conclusions: NGAL is a good predictor of early AKI post OLT although there is considerable variation in the published results. Further studies with prospectively defined cut-off values, standardized definitions of AKI and rigorous data reporting should be conducted to establish its clinical usefulness and limitations. Highlights: Acute kidney injury is common post liver transplant surgery. NGALs show promise at predicting AKI early. Significant variability exists between the studies. Further trials are necessary. Early diagnosis may improve outcomes for these patients.